2020
DOI: 10.3949/ccjm.87a.ccc024
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathy in COVID-19: Manifestations and management

Abstract: The statements and opinions expressed in COVID-19 Curbside Consults are based on experience and the available literature as of the date posted. While we try to regularly update this content, any offered recommendations cannot be substituted for the clinical judgment of clinicians caring for individual patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
23

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 41 publications
2
68
0
23
Order By: Relevance
“…Therefore, early elevated plasma fibrinogen level may be a risk marker for the severe acute respiratory syndrome development 42 . But there are also authors who found normal plasma fibrinogen levels 41 . Moreover, they consider that high level of plasma D-dimer that coexists with normal fibrinogen levels is a characteristic finding in these patients and correlates with the disease severity and thrombotic risk 41 .…”
Section: Plasma Fibringen and D-dimer Levelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, early elevated plasma fibrinogen level may be a risk marker for the severe acute respiratory syndrome development 42 . But there are also authors who found normal plasma fibrinogen levels 41 . Moreover, they consider that high level of plasma D-dimer that coexists with normal fibrinogen levels is a characteristic finding in these patients and correlates with the disease severity and thrombotic risk 41 .…”
Section: Plasma Fibringen and D-dimer Levelsmentioning
confidence: 99%
“…But there are also authors who found normal plasma fibrinogen levels 41 . Moreover, they consider that high level of plasma D-dimer that coexists with normal fibrinogen levels is a characteristic finding in these patients and correlates with the disease severity and thrombotic risk 41 . A level of D-dimer more than 6 times higher than the upper limit of normal values can be found in patients with the highest thrombotic risk 41 .…”
Section: Plasma Fibringen and D-dimer Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…COVID-19 is a multisystem disease which increases risk of coagulopathy and thus, venous thromboembolism (VTE) and pulmonary embolism (PE) in critically ill patients. The incidence rate for VTE and arterial thrombosis and related thrombo-embolic complications remain very high in COVID-19 patients [ 1 ]. There are three possible mechanisms associated with this observation: (1) through cytokine storm by interleukin-1, interleukin-6, tumor necrosis factor-alpha and others leading to endothelial activation and widespread thrombosis as seen in pulmonary vessels in acute respiratory distress syndrome; (2) severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has shown an affinity for angiotensin-converting enzyme 2 located at alveolar epithelial cells, endothelial cells of extrapulmonary tissues leading to thrombosis by microvascular injury and multiorgan failure; and (3) lupus anticoagulant antibodies can lead to thrombosis by the “two hit” thrombosis model [ 1 ].…”
Section: Introductionmentioning
confidence: 99%